Research trends and hotspots of metabolites and inflammatory bowel disease: a bibliometric analysis - Lyu, Jia-Qi; Xiao, Fang-Jun; Wang, Ke-Ying; Liu, Ying-Jie; Hui, Jing-Mei; Lin, Jie (Frontiers in Microbiology, 2025)
PurposeThe purpose of this study is to analyze the current research status and explore the relationship between metabolites and inflammatory bowel disease (IBD), providing insights for future research.MethodsIn this study, we retrieved publications on metabolites and IBD from the Web of Science Core Collection (WOSCC), covering the period from 1994 to 2024. We conducted descriptive and visual analyses of the topics, journals, countries/regions, institutions, authors, and citation counts of these publications.ResultsFrom January 1994 to June 2024, a total of 509 relevant publications were retrieved from the WOSCC, with the number of publications steadily increasing each year. These articles were published in 222 journals, with the top three most productive journals being inflammatory bowel diseases (36 publications), Alimentary Pharmacology & Therapeutics (16 publications), and Digestive Diseases and Sciences (13 publications). The leading countries in publication output were China (154 publications, 30.3%), the USA (101 publications, 19.8%), and the UK (32 publications, 6.3%), with total citation counts of 3,175, 7,439, and 1,444, respectively. The most recent trending keywords in this field include “gut microbiota,” “inflammation,” and “pathogenesis.”ConclusionRecent research on the relationship between metabolites and inflammatory bowel disease (IBD) has grown significantly, deepening our understanding of their connection. Further exploration of this relationship could not only enhance the quality of life for IBD patients but also offer new insights into potential cures for the disease.